Enhancing learners' motivation and interest in the EFL classroom / Ruba Murad Mahfouz Siaj and Mohammed A A Farrah - Mahfouz Siaj, Ruba Murad; Mohammed A, A Farrah (Universiti Teknologi MARA, Kedah, 2021)
The present study investigated the attitudes of EFL students towards the idea of motivation and some influences that enhance their motivation in the EFL context. 71 EFL students from the English Department at Hebron University in Palestine participated in the study and completed a 25-item questionnaire. In addition, interviews were held with five EFL instructors from Hebron University to see what motivational strategies they use in EFL classrooms. Also, they were asked to give their opinions regarding different motivational aspects. The results indicated that the students are intrinsically and extrinsically motivated to learn English. Moreover, there was a general agreement between the motivational methods that the teachers use and the preferences of their students. Besides, the students indicated that some boring educational methods should be omitted and replaced by other motivational ones which have matched some of the teachers' opinions regarding that some changes in the curriculum and the way of teaching should be taken into consideration.